A clinically suspected case of thrombotic thrombocytopenic purpura managed with therapeutic plasma exchange in Kathmandu Medical College Teaching Hospital - Adhikary, I.P.; Pokhrel, A.; Bhattarai, T.; Bhusal, Y.; Acharya, S.; Khanal, A. (Journal of Advances in Internal Medicine, 2019)
Thrombotic thrombocytopenic purpura (TT P) is a life threatening thrombotic microangiopathy which may not present with the classic pentad of microangiopathic hemolytic anemia, fever, neurologic changes, thrombocytopenia and renal dysfunction. High level of clinical vigilance has to be rendered in suspected cases of TT P and therapeutic plasma exchange (TPE) must be started as soon as possible as this can be a lifesaving intervention. TT P is a category 1 recommendation for plasmapheresis as per the guidelines from American Society for Apheresis (ASFA). We present a case of 55 years old male who presented with abdominal pain, vomiting and fever and was clinically suspected as a case of thrombotic thrombocytopenic purpura. He received an intensive care treatment (endotracheal intubation with mechanical ventilation and renal replacement therapy) and after no improvement following fifth day of treatment, he was started on therapeutic plasma exchange (TPE). After two cycles of plasmapheresis, he had marked clinical improvement. Due to the cost unaffordability by the patient›s family, further sessions of plasma exchange therapy could not be done. The patient was later discharged and followed up in outpatient basis.